2013
DOI: 10.1074/jbc.m113.518803
|View full text |Cite
|
Sign up to set email alerts
|

NDUFAF7 Methylates Arginine 85 in the NDUFS2 Subunit of Human Complex I

Abstract: Background: Arginine 85 of NDUFS2, a subunit of mitochondrial complex I, is symmetrically dimethylated.Results: NDUFAF7, a protein methylase in the matrix of mitochondria, modifies arginine 85 of NDUFS2 during assembly of complex I.Conclusion: Methylation of arginine 85 of NDUFS2 is required for assembly of complex I.Significance: The arginine protein methylase, NDUFAF7, is an assembly factor for human complex I.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

2
115
0

Year Published

2013
2013
2020
2020

Publication Types

Select...
10

Relationship

2
8

Authors

Journals

citations
Cited by 94 publications
(117 citation statements)
references
References 83 publications
2
115
0
Order By: Relevance
“…How these assembly factors function is not known, but they may stabilize the subcomplexes and help to join them to other subcomplexes to build the complete enzyme. Two additional proteins involved in the assembly of complex I, C20orf7 (NDUFAF5) and MidA (NDUFAF7), are predicted to be protein methyltransferases and NDUFAF7 methylates subunit NDUFS2 (39,40). Ind1 is involved in the assembly of iron-sulfur clusters in complex I and C8orf38 (NDUFAF6) stabilizes subunit MT-ND1 (41, 42).…”
Section: Discussionmentioning
confidence: 99%
“…How these assembly factors function is not known, but they may stabilize the subcomplexes and help to join them to other subcomplexes to build the complete enzyme. Two additional proteins involved in the assembly of complex I, C20orf7 (NDUFAF5) and MidA (NDUFAF7), are predicted to be protein methyltransferases and NDUFAF7 methylates subunit NDUFS2 (39,40). Ind1 is involved in the assembly of iron-sulfur clusters in complex I and C8orf38 (NDUFAF6) stabilizes subunit MT-ND1 (41, 42).…”
Section: Discussionmentioning
confidence: 99%
“…These cytoplasmic and nuclear enzymes have been shown to complement protein lysine methyltransferases and indeed perhaps even protein kinases in modulating transcriptional activation/repression and controlling mRNA splicing, DNA repair, the cell cycle, and signaling pathways (13,15,40,82). A mitochondrial seven-beta strand methyltransferase from an unrelated family, designed NDUFAD7, modifies a subunit of complex I in the mammalian electron transport chain (83,84). All of these enzymes modify only the terminal ω-nitrogen atoms of the arginine residue.…”
Section: An Unusual Protein Arginine Methyltransferase That Modifiesmentioning
confidence: 99%
“…29,30 Although these four mutations have been found to be related to other diseases and no evidences so far indicates that they are involved in myopia according to their function, we still could not exclude their contribution to myopia develompent in such a small pedigree. Whereas in the case of NDUFAF7, as a mitochondrial assembly factor, it is involved in mitochondrial respiratory chain system, 31 and previous research showed that the decline in ATP synthesis via mitochondrial energy metabolism leads to severe visual impairment. 32 Thus, we decided to focus on the function investigation of the mutant (MT) NDUFAF7 detected as a de novo missense mutation (p.D266E) in this family.…”
mentioning
confidence: 99%